Pemanfaatan Formula Kinang untuk Pembentukan Permen Jeli Fungsional - Pambayun, Rindit; Ferdinan, Muhammad; Santoso, Budi; Widowati, Tri Wardani; Puspa Dewi, Siti Rusdiana (Seminar Nasional Lahan Suboptimal, 2018)
Pambayun et al, 2019. Utilization of Betel Chewinging Formulation for Processing of Functional Jelly Candy. pp. 156-164.The research objective was to develop jelly candy having antioxidant and antibacterial properties by utilizing betel chewinging formulation. Method used in this research was factorial randomized block design with two treatment factors and two replications. The first factor was betel chewinging formulation (A) consisting of A1 = 2%, A2 = 4%, and A3 = 6% (b/v) and the second factor was gelatin concentration (B) consisting of  B1= 15%, B2= 20% and B3 = 25 % (b/v).  The results showed that jelly candy contains total phenol with magnitude of 41.39 mg/L to 61.83 mg/L, inhibition power diameter (DDH) Streptococcus mutans bacteria in the range of 9.67 mm to 16.67 mm, antioxidant with IC50 value in the range of 1,572.78 ppm to 1,117.96 ppm, lightness of 17.50% to 32.47%, chroma of 2.97% to 3.97%, hue value of 20.73o to 26.07o, texture of 692.03 to 1,654.67 (gf) and solubility of 3.87 to 7.00 minutes.